ANALYSIS OF FACTORS AFFECTING PURCHASING INTENTION ONLINE FOOD DELIVERY - Afridhianika, Annisa Nugraheni; Harisudin, Mohamad; Handayani , Sugiharti Mulya (LPPM Universitas Duta Bangsa Surakarta, 2023)
The purpose of this study was to determine the effect of E-Service Quality, sales promotion, and trust on the buying interest of Shopee Food consumers. Quantitative research methods, sampling using purposive sampling method techniques. The research subjects were 100 students from Sebelas Maret University, Universitas Muhammadiyah Surakarta, Universitas Surakarta, Universitas Slamet Riyadi and Universitas Duta Bangsa Surakarta. Analysis in research using Structural Equation Modeling (SEM). Based on the results of the analysis, it is known that there is a significant effect of E-Service Quality, sales promotion, and E-Trust on buying interest. This means that the variables E-Service Quality, sales promotion, and E-Trust, can measure buying interest. The better the E-Service Quality, sales promotion, and E-Trust, the higher the purchase intention. The results of the mediation test show that E-Trust affects the relationship between E-Service Quality and sales promotion with the purchase intention of Shopee Food consumers. The results of this study can be used as input material for a marketing strategy for market place platforms by optimizing aspects of E-Service Quality, sales promotion Brand Image and trust because these variables are proven to increase consumer buying interest.